ANALISIS YURIDIS PELAKSANAAN PRINSIP NIRLABA DALA BADAN HUKUM YAYASAN YANG BERGERAK DIBIDANG PENDIDIKAN (STUDI PADA YAYASAN TEUKU LAKSAMANA HAJI IBRAHIM LUENG PUTU, PIDIE JAYA) - RINALDIANSYAH - (PREMISE LAW JURNAL, 2017)
ABSTRACT A foundation is established not for commercial or profit sake, but to help or improve people’s life prosperity.When the society has a willing to establish a social foundation with social, religious and humanitarian purposes, or which purpose is for charity instead of seeking profit, they will become the establisher, manager, and supervisor of the Foundation. The thesis uses legal certainty theory. It employs normative juridical research method with descriptive analysis and refers to the legal provisions, legal documents and books related to the research problems. A legal entity which may manage education based on the Law on SISDIKNAS is the non-profit Legal Entity which acts as the education organizer. A foundation, a association, and other similar entities which have status of legal entity, remain to organize an education unit as long as they do not violate the legal provisions which regulate non-profit legal entity. The role and function of the Foundation managers in the implementation of non-profit principle are to carry out their duties with good intention, without causing loss or negligence, with full responsibility, and to pay everyone who contributes their time, energy, and intelligence to the Foundation. Keywords: Foundation, National Education System, Non-profit Principle